Population of Rafflesia in Maninjau Natural Reservoirs, Nagari Baringin - Palembayan, Agam Regency - Yustri Vikasi; Nurhasan Syah; Annisa Firdaus (Pascasarjana, Universitas Negeri Padang, 2020)
Rafflesia is one of the plants with unique properties and at the same time keeps a mystery to plants. The purpose of this study was to determine the distribution map of Rafflesia and Rafflesia individuals. The research was conducted in May 2018 in the Maninjau Nature reserve, Nagari Baringin in Palembayan sub-District, Agam Regency. The method used in thisstudy is Purposive sampling by making a sample plot measuring 25 x 25 meters in 16 plots to become 1 hectare, by measuring diameter know, scar and wart or boil and countingthe number of individuals of the Rafflesia. The results of this studyare the distribution of Rafflesia only in plot 1 and plot 2 with a population of 4 populations with the number of individuals in population 1 as many as 9 individuals, population 2 as many as 6 individuals, population 3 as many as13 individuals and in population 4 a total of 7 individuals were foundin the form of warts, knots, scars, and rotten flowers.